Comportamento reprodutivo, territorial e vocalização de Hypsiboas atlanticus (CARAMASCHI & VELOSA, 1996) (ANURA: HYLIDAE) no baixo Sul da Bahia, BRASIL - Guimarães, Felipe Camurugi Almeida (2012)
Although the ad call is the most studied among anuran species, few studies have reported two distinct ad calls for the same species. Hypsiboas atlanticus has two types of announcement call, issued according to the vocalization micro-habitat (perch or partly in the water), in addition to a meeting corner and cutting corner. Although the characteristics of the two types of ad corner allow for unambiguous differentiation, the function of these two corners remains unknown. The anurans' vocalization and social behavior are closely related to reproduction, therefore, understanding the reproductive biology of H. atlanticus, as well as the social behavior among males, may suggest how the two types of advertisement call act in this species. This work aims to verify how the males of H. atlanticus use the two micro-habitats throughout the night and how to defend territories in these micro-habitats, in addition to studying the reproduction of the species, through the spawning characteristics, sexual dimorphism and mating. Therefore, a population of H. atlanticus in the Michelin Ecological Reserve, municipality of Igrapiuna, BA, was studied during the period from July 2009 to August 2011. The species vocalized during all the months of observation. Temperature and humidity influenced the male abundance in water and perch throughout the night. The monthly abundance of the species was not related to precipitation. Males were significantly larger and heavier than females and this dimorphism seems to influence behavior during oviposition. The size of the eggs was significantly related to the mass of the female. Perched males showed little change in the ad corner when stimulated by “playback”, but responded with meeting corner and visual cues. Males in the water increased the intensity or the number of notes when stimulated with “playback”. Judging by the time of the males' most active activity on the perch (early evening) and the responses to the “playback”, the ad singing on the perch seems to have more territorial information, while the ad singing on the water, mating place , seems to be the most attractive for females.